2012
DOI: 10.1038/modpathol.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

High expression of prostate-specific membrane antigen in the tumor-associated neo-vasculature is associated with worse prognosis in squamous cell carcinoma of the oral cavity

Abstract: Prostate-specific membrane antigen (PSMA) is a transmembrane protein expressed in prostate cancer as well as in the neo-vasculature of nonprostatic solid tumors. Here, we determined the expression pattern of PSMA in the vasculature of oral squamous cell carcinoma. Using a previously validated antibody, PSMA staining distribution and cyclooxygenase 2 (COX2) expression status was evaluated in a cohort of patients with squamous cell carcinoma of the oral cavity (n ¼ 96) using immunohistochemistry and was correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 30 publications
1
56
2
1
Order By: Relevance
“…Another 2 studies were also excluded due to lack of data integrity (Figure 1). Eventually, 12 clinical cohort studies with a total of 979 oral cancer patients met our inclusion criteria for quantitative data analysis [8, 11, 18, 19, 21–23, 2731]. There were 5 independent analyses focused on the prognosis of oral cancer, some of which were divided into two groups, including COX2-positive group ( n = 157) and COX2-negative group ( n = 254).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another 2 studies were also excluded due to lack of data integrity (Figure 1). Eventually, 12 clinical cohort studies with a total of 979 oral cancer patients met our inclusion criteria for quantitative data analysis [8, 11, 18, 19, 21–23, 2731]. There were 5 independent analyses focused on the prognosis of oral cancer, some of which were divided into two groups, including COX2-positive group ( n = 157) and COX2-negative group ( n = 254).…”
Section: Resultsmentioning
confidence: 99%
“…To be specific, the upregulation of COX2, at both mRNA and protein levels, may result in the enhanced synthesis of prostaglandins, increasing proliferative activity of neoplastic cells, and further accelerating angiogenesis and inhibiting immune surveillance; additionally, immunohistochemical overexpression of COX2 may thereby inhibit apoptosis and strength invasiveness [27]. In this regard, high expression levels of COX2-derived prostaglandin can be identified to be active in highly vascularized tumors, and in turn selective suppression of COX2 could lead to a decreased tumor growth because of the transformation in the neovasculature [23]. Therefore, we can postulate that the elevated expression of COX2 may have an important role in predicting the clinical outcome in oral cancer, and these many essential processes in carcinogenesis make COX2 an attractive therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This opposite gene modulation may favor the angiopoietin 1 (ANGPT1)-TIE2 interaction and, together with the down-modulation of VEGFR1 (FLT1) and VEGFR2 (KDR), drive a physiological normalization of the vasculature at tumor site [2]. This hypothesis is also supported by the findings that genes encoding for proteins expressed by endothelial precursor cells or by the tumor-associated neo-vasculature such as Folate receptor 1 (FOLH1, known also as PMSA), CXCR7 and ESM1, [3-6] were also down-modulated. Gene profiling also revealed that in cediranib treated ASPS, CCL2 mRNA was associated to the presence of high level of CD163 gene expression.…”
Section: Commentarymentioning
confidence: 99%
“…Immunohistochemical studies reported that PSMA is strongly expressed by normal and neoplastic prostatic epithelium, along with the epithelium of other genitourinary organs (bladder, kidney, fallopian tubes) and intestine 3–5 . Several recent studies found that PSMA could be expressed not only by epithelial cells, but also by vascular endothelium of various malignancies including oral 6 , gastric and colorectal 7 , lung 8 , breast 9 , endometrial and ovarian 10 , renal 11 , urothelial 12 , and glial tumors 13, 14 .…”
Section: Introductionmentioning
confidence: 99%